Changes in the composition of publicly traded firms: Implications for the dividend-price ratio and return predictability - Stephan Jank (University of Cologne, Centre for Financial Research (CFR), 2012)
This article documents how the changing composition of U.S. publicly traded firms has prompted a decline in the long-run mean of the aggregate dividend-price ratio, most notably since the 1970s. Adjusting the dividend-price ratio for such changes resolves several issues with respect to the predictability of stock market returns: The adjusted dividend-price ratio is less persistent, in-sample evidence for predictability is more pronounced, there is greater parameter stability in the predictive regression (particularly during the 1990s), and there is evidence of out-of-sample predictability.
Keywords: G10; G12; G14; G35; 330; return predictability; dividend-price ratio; payout policy; sample selection; choice of organizational structure